2005
DOI: 10.1161/01.hyp.0000168046.19884.6a
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ-Activating Angiotensin Type-1 Receptor Blockers Induce Adiponectin

Abstract: Abstract-The adipose-specific protein adiponectin has been recently discovered to improve insulin sensitivity.Angiotensin type-1 receptor (AT1R) blockers (ARBs) reduce the incidence of type 2 diabetes mellitus by mostly unknown molecular mechanisms. To identify new antidiabetic mechanisms of ARBs, we studied the regulation of adiponectin by angiotensin II (Ang II) and different ARBs in murine 3T3-L1 adipocytes and obese Zucker rats. Adiponectin protein expression was markedly stimulated by Ang II (5 nmol/L), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
192
3
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(211 citation statements)
references
References 25 publications
10
192
3
3
Order By: Relevance
“…It has been reported that RAS inhibitors 25,26 and CCBs 27 increase adiponectin levels in non-hemodialysis patients. Previous studies have shown that angiotensin II receptor blocker inhibits obesity-induced hypoadiponectinemia through the inhibition of reactive oxygen species generation in mice 28 and that some angiotensin II receptor blockers have peroxisome proliferator-activated receptor g-activating properties, 29 thereby stimulating adiponectin production. Some CCBs have also been reported to have the ability to increase adiponectin levels through the inhibition of reactive oxygen species generation 30 and of monocyte and platelet activation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that RAS inhibitors 25,26 and CCBs 27 increase adiponectin levels in non-hemodialysis patients. Previous studies have shown that angiotensin II receptor blocker inhibits obesity-induced hypoadiponectinemia through the inhibition of reactive oxygen species generation in mice 28 and that some angiotensin II receptor blockers have peroxisome proliferator-activated receptor g-activating properties, 29 thereby stimulating adiponectin production. Some CCBs have also been reported to have the ability to increase adiponectin levels through the inhibition of reactive oxygen species generation 30 and of monocyte and platelet activation.…”
Section: Discussionmentioning
confidence: 99%
“…However, contradictory data exist regarding the effects of AII and ARB on adipocyte gene expression. Clasen et al demonstrated that ARBinduced adiponectin protein expression was mediated via PPARc, whereas AII itself increased adiponectin production in 3T3-L1 adipocytes (32). Moriuch et al reported that neither AII nor candesartan had any effect on adiponectin promoter activity, and that another ARB, telmisartan, stimulated adiponectin transcription independent of PPARc (33).…”
Section: Discussionmentioning
confidence: 99%
“…One such approach is the pharmacological blockade of the AT1R by losartan, which in contrast to other AT1R blockers, like telmisartan, does not display additional peroxisome proliferator-activating receptor (PPAR)␥ agonistic effects (9). Here we investigate the role of the RAS during autoimmune inflammation of the CNS in the model of myelin oligodendrocyte glycoprotein-induced experimental autoimmune encephalomyelitis (MOG-EAE), which mimics many aspects of multiple sclerosis (10).…”
mentioning
confidence: 99%